SOCIAL MEDIA’S INFLUENCE ON PUBLIC OPINION: A MASS COMMUNICATION ANALYSIS - St. Rahmah; Syarifuddin; Indah Sulistiani (Jurnal Komunikasi, 2024)
Because social media has a number of qualities that make it useful in influencing public opinion, it has a big impact on public opinion. Social media itself provides a powerful platform for sharing ideas and information, of course the impact on public opinion has very significant positive and negative sides. Therefore, it is important for social media users to be wise in using social media. The presence of modern communication media as a result of the increasing development of information and communication technology tends to blur the boundaries between interpersonal communication or traditional interpersonal communication and mass communication. The method used in this article is to use a literature study which contains theories related to the problem being studied. The impact of social media on public opinion, as well as the variables that affect its function and its problems and effects, are all covered in this study